LAYERED MAFIC SILL COMPLEX BENEATH THE EASTERN SNAKE RIVER PLAIN: EVIDENCE FROM CYCLIC GEOCHEMICAL VARIATIONS IN BASALT - Shervais J.W.; Vetter S.K.; Hanan B.B. (My University, 2006)
The eastern Snake River Plain in southern Idaho, western United States, is characterized by 1-2 km of Pleistocene to late Pliocene basalt overlying rhyolite caldera complexes. Cyclic variations in the chemical composition of basalts from 1136 m of scientific drill core show that the parent magmas of these lavas evolved by crystal fractionation at shallow to intermediate crustal depths, punctuated by episodic recharge with more primitive compositions and assimilation of adjacent wall rock. We have identified 10 upward fractionation cycles and four reversed cycles; assimilation of sialic crust was limited and mainly affects the oldest basalts, which directly overlie rhyolites. We infer that the crystal fractionation and/or recharge cycles took place in a series of sill-like intrusions at intermediate crustal depths that now form a layered mafic intrusion that underlies the eastern Snake River Plain at depth. This layered sill complex is represented by the ~10-km-thick "basaltic sill" that has been imaged seismically at ~12-22 km depth. The association of this mid-crustal sill complex with geochemical fractionation cycles in basalt supports the concept that exposed layered mafic intrusions may be linked to overlying basalt provinces that have since been removed by erosion. © 2006 Geological Society of America.
Keywords: BASALT; BASALTIC VOLCANISM; CRUSTAL STRUCTURE; LAYERED INTRUSIONS; Pleistocene; Pliocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен